(untitled) (Journal of the College of Basic Education, 2025)
This study aimed to identify the nature of the organizational challenges facing the implementation of school tournaments for female students in the educational directorates of Baghdad, by exploring the perspectives of female physical education teachers as the direct actors involved in organizing such events.The research problem lies in the fact that despite the efforts made by the Baghdad directorates to hold school sports tournaments for girls, practical reality reveals the presence of multiple organizational challenges that may hinder the optimal conduct of these tournaments.The study adopted the descriptive survey method and developed a customized scale that included seven main domains of challenges: administrative and organizational, human resources, financial, infrastructure, socio-cultural, time and scheduling, and regulatory and legal frameworks.The instrument was applied to a sample of (126) teachers from various educational directorates in Baghdad, and the data were analyzed using the one-sample t-test to determine the significance of the response levels.The results showed that the most influential challenges from the teachers’ perspectives were the socio-cultural challenges, followed by infrastructure-related challenges, and time and scheduling challenges, all of which had a high level of statistical significance. In contrast, the administrative, human, and organizational challenges did not show statistical significance, indicating that they are not currently considered major barriers. Additionally, financial challenges appeared at a moderate level but with statistical significance.The study concluded that organizing school sports tournaments for girls still faces multiple obstacles primarily related to cultural and societal structures, as well as inadequate school environments. The study recommended several measures, most notably enhancing infrastructure, allocating financial resources, revising regulatory frameworks, and raising community awareness of the importance of sports for girls.